Dental Acrylics - Potential Agent for a Myriad of Diseases - Shivangi Gajwani; D Krishna Prasad; N Sridhar Shetty; Manoj Shetty (Wolters Kluwer Medknow Publications, 2007)
An allergic reaction also known as a hypersensitivity reaction is caused by the immune system in response to a foreign substance (or allergen). Allergenic chemicals can be found in many products used in the dental operatory. With repeated exposure, these chemicals can cause allergic reactions in dental professionals, resulting in local as well as systemic manifestations. According to various studies done, it became evident that the prevalence of acrylic allergy most commonly in the form of allergic contact dermatitis is affecting the dental personnel to a much greater degree than is believed. Awareness of this disease complex in the form of any new symptoms and potential exposure is paramount for dental personals.